Flow cytometry in the diagnosis of plasma cell tumors and assessment of minimal residual disease - L. Yu. Grivtsova; T. Yu. Mushkarina; V. V. Lunin; P. A. Zeynalova (Онкогематология, 2021)
The article considers the features and possibilities of flow cytometric diagnostics of plasma cell neoplasms, taking into account the classification of lymphoid and hematopoietic tissue tumors of the World Health Organization, revision of 2017 and the NCCN clinical recommendations, 2021. Standardized flow cytometric protocols (the Euro-Flow conception) and algorithms for both the diagnosis of plasma cell tumors and the detection of minimal residual disease in plasma cell myeloma are described.